1999
DOI: 10.1107/s0907444998008658
|View full text |Cite
|
Sign up to set email alerts
|

Purification and crystallization of a novel membrane-anchored protein: theSchistosoma haematobiumserpin

Abstract: A unique serine-protease inhibitor (serpin) of the blood¯uke S. haematobium has been crystallized. It is an antitrypsin with an unusual residue (phenylalanine) at its reactive center. Unlike any known member of this gene family, it is a membrane-anchored protein on the surface of the parasite. The location of this serpin and immunological response to the protein indicate that it may play a important role in host±parasite interaction. The crystals belong to the trigonal space group P3 2 21 or P3 1 21 with unit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The expression of histidine-tagged ShSPI in Escherichia coli and purification of the protein have been described previously (Huang et al, 1999). ShSPI was crystallized by the vapourdiffusion method using a sitting-drop setup.…”
Section: Preparation and Crystallization Of Shspimentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of histidine-tagged ShSPI in Escherichia coli and purification of the protein have been described previously (Huang et al, 1999). ShSPI was crystallized by the vapourdiffusion method using a sitting-drop setup.…”
Section: Preparation and Crystallization Of Shspimentioning
confidence: 99%
“…The S. haematobium serpin (henceforth designated ShSPI, corresponding to UniProt entry Q26502) has been crystallized previously and data were collected to a resolution of 2.4 Å (Huang et al, 1999). Here, we report the determination of its three-dimensional structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A membrane-anchored serpin of Schistosoma haematobium has antitrypsin activity. The complex formed between the membrane-embedded Schistosoma japonicum serpin and human trypsin allows the parasite to reduce the immunogenicity of its exposed serpin and may help it to evade the immune defenses (Huang et al 1999). These results collectively suggest that serpins of helminthic parasites play important roles not only in parasite physiology but also in interactions with their hosts.…”
Section: Introductionmentioning
confidence: 56%
“…Serpins have been identified in several helminthic parasites including Ascaris lumbricoides (Goodman and Peanasky 1982), Schistosoma mansoni (Ghendler et al 1994), Schisotosoma haematobium (Blanton et al 1994), Brugia malayi (Yenbutr and Scott 1995), and Echinococcus granulosus (Shepherd et al 1991). Their biological roles are not completely understood, but several studies have suggested their essential roles in host-parasite interactions such as host immune evasion and protection from proteolytic attack by host proteases (Martzen et al 1985;Ghendler et al 1994;Huang et al 1999;Zang et al 1999;Zang et al 2000;Merckelbach and Ruppel 2007).…”
Section: Discussionmentioning
confidence: 97%